Synthesis of Tri- and Tetra- Phenyl Substituted 1H-imidazoles in the Presence of Chitin and Pectin as Natural Catalyst - Marandi, Ghasem; Rasoulizadeh, Salmeh; Maghsoodlou, Malek T. (Current Catalysis, 2021)
Introduction: Chitin and pectin are important natural polymers which are used as a natural catalyst for the synthesis of tri- and tetra- phenyl substituted 1H-imidazoles. Materials and Methods: The reaction of benzil and aromatic aldehydes with ammonium acetate in the presence of chitin produces 2,4,5-triphenyl-1H-imidazoles and the reaction of benzil, aromatic aldehydes and aniline derivatives with ammonium acetate in the presence of pectin produces 1,2,4,5- tetraphenyl-1H-imidazoles, respectively. Results: The results show that the synthesis of 2,4,5-triphenyl-1H-imidazoles and 1,2,4,5-tetraphenyl- 1H-imidazoles can be catalyzed by chitin and pectin in an effective route, respectively. All synthesized compounds are in good agreement with previously reported compounds. Conclusion: In conclusion, an efficient methodology has been carried out to generate 2,4,5-triphenyl- 1H-imidazoles and 1,2,4,5-tetraphenyl-1H-imidazoles, by using non-toxic, cheap and in available catalysis (chitin and pectin).
Keywords: benzil